A systematic evaluation of single cell RNA-seq analysis pipelines - Beate Vieth (Nature Portfolio, 2019)
There has been a rapid rise in single cell RNA-seq methods and associated pipelines. Here the authors use simulated data to systematically evaluate the performance of 3000 possible pipelines to derive recommendations for data processing and analysis of different types of scRNA-seq experiments.